The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/jace.16521
|View full text |Cite
|
Sign up to set email alerts
|

Single‐step preparation of rutile‐type CrNbO4 and CrTaO4 oxides from oxalate precursors–characterization and properties

Abstract: Chromium niobate and tantalate (CrNbO4 and CrTaO4) were synthesized by pyrolysis of the oxalate‐based heterometallic complexes [Cr2(bpy)4(μ‐O)4Nb2(C2O4)4]·3H2O (Cr‐Nb) and [Cr(bpy)2(H2O)(μ‐O)Ta(C2O4)3]2·3.5H2O (Cr‐Ta) (bpy = 2,2'‐bipyridine). Compared to conventional solid‐state synthesis, herein studied oxides are prepared at lower temperatures, in one step without repeating grinding procedures. The structure, morphology, and optical properties of the as‐synthesized oxides were characterized using powder X‐ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Experimental results from ref. 38 indicated that CrTaO 4 possesses a rutile‐type structure. It is well‐established that the prototype of the rutile phase is TiO 2 , which exhibits a space group of P 4 2 / mnm .…”
Section: Computational Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental results from ref. 38 indicated that CrTaO 4 possesses a rutile‐type structure. It is well‐established that the prototype of the rutile phase is TiO 2 , which exhibits a space group of P 4 2 / mnm .…”
Section: Computational Results and Discussionmentioning
confidence: 99%
“…The results depicted in Figure 2b indicate that the C 2/ m structure remains the most stable phase in the entire temperature range from 0 to 2000 K followed by the I 4 1 md and P 2/ c phase, but the difference in total energy is extremely small, 0.002 eV/atom, which is well within the uncertainty range of DFT calculations especially for oxides. Various experimental results show that the stable crystal structure for CrTaO 4 is the rutile I 4 1 md 37,38 . There are several reasons that may contribute to the discrepancy in the phase stability of CrTaO 4 between DFT prediction and experiments.…”
Section: Computational Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From Fig. 1(a), one can see that the hallmark in the TG curve is a mass loss of about 0.358%, which can be attributed to the evaporation of Cr 2 O 3 at high temperatures [24]. In the DSC curve, there is a wide exothermic peak in the temperature range of 1030−1110 ℃.…”
Section: Synthesis and Characterization Of Crtaomentioning
confidence: 93%
“…This paper outlines the use of the CP [Cu II Fe II 2 (H 2 O)(terpy)(C 2 O 4 ) 3 ] n ( 1 ; terpy = 2,2′:6′,2″‐terpyridine) 25 as an efficient photocatalyst for the photodegradation of rhodamine B (RhB, C 28 H 31 ClN 2 O 3 ) and methylene blue (MB, C 16 H 18 N 3 SC) dye pollutants, as well as a single molecular precursor for the preparation of the CuFe 2 O 4 spinel due to the suitable metal ratio by thermal treatment 26–30 . Namely, the oxalate group, C 2 O 4 2− , easily decomposes at low temperatures into gaseous CO 2 and CO, and therefore, the oxalate‐based solids can serve as suitable precursors for the preparation of mixed metal oxides 11,26,28,31–33 . In this work, we are the first ones to deliver a brief scheme on developing the feasible molecular precursor‐to‐material route for the preparation of CuFe 2 O 4 spinel as viable alternative to various hydrothermal/solvothermal pathways.…”
Section: Introductionmentioning
confidence: 99%